Deslindes literarios : Juan Goytisolo, el romancero, José Emilio Pacheco, José Gorostiza, Alejo Carpentier, Reinaldo Arenas, Roberto Arlt, Roman Jakobson - Mora Sánchez, Blanca Elvia, 1948-1974 (Jornadas, 1977)
Colección de trabajos sobre diversas calas en varios objetos literarios de la cultura en lengua española.